Chemical Composition of Leaf Essential Oil of Cinnamomum porrectum (Roxb.) Kosterm. Issue 5 (3rd September 2019) - Qiu, Fengying; Yang, Haikuan; Zhang, Ting; Wang, Xindong; Wen, Shifang; Su, Xiaohua
Abstract: Cinnamomum porrectum (Roxb.) Kosterm is an important plant which produces natural essential oil. In this study, essential oil was hydro-distilled from leaves of five different samples of C. porrectum which were randomly selected in a C. porrectum forest in Guangdong Province of China, and identified by Gas Chromatography Mass Spectrometry (GC/MS). The results revealed that the average yield of essential oil was 1.12 % (v/w). A total of 65 compounds were identified from five samples, and 31 of which were reported for the first time in leaf essential oil of C. porrectum . High contents of monoterpenes and sesquiterpenes were found in the leaves of C. porrectum . The main components of essential oil were linalool (79.4 %), elemol (38.1 %), eucalyptol (35.6 %), β-caryophyllene (34.6 %), camphor (33.2 %), α-eudesmol (26.5 %), citral (23.5 %) and L-α- Terpineol (22.0 %). Different types of high-value compounds were found to be present in the five selected samples of C. porrectum oil, and the difference of essential oil components in individual leaves was remarkable. The various breeding techniques can be utilization based on different chemical types of leaf essential oil to exploit the plant to its full potential.